The Intsomi Ambassadors: using communicative ecologies to enhance home literacy practices amongst working class parents in Grahamstown - Gush, Cathy (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2019)
Utilising theories of Communication for Development, the research explores how literacy practices in the homes of a group of working class, English second language parents in Grahamstown are affected by the introduction of new literacy material and insights Furthermore, it discusses how, and through which forms of media, these observed dynamics and changes in practice are best communicated to similar households. The issue of children's literacy development in South Africa is of serious concern, in particular the role that parents play and the level of support they give through home literacy practices. The context is one in which South African children have performed very poorly with regard to literacy levels in international benchmark testing as well as in national assessments. The summary report on the Progress in International Reading Literacy Study (PIRLS) found that some of the factors contributing to these poor results were the lack of reading resources in homes, as well as the lack of strong home-school partnerships in which parents took up the role of co-educators, or even of primary educators at the preschool stage. A group of parents employed by Rhodes University at the Grade 1 - 5 levels signed up to be the recipients of a programme supporting the literacy development of their primary and pre-primary school children. The Intsomi Project is run by the Rhodes Community Engagement Office as part of the Vice-Chancellor's Education Initiative and provides close to 100 families with weekly reading material and educational games for their children, as well as workshops on the use of these materials and how they might benefit the children. Following a Participatory Action Research approach, a "vanguard" group of parent participants, known as the Intsomi Ambassadors, developed their role as literacy activists, becoming co-creators of media messages that utilised and built on the first stage of their communication within the group. The research explored how the principles and techniques of development support communication, and those of communicative ecologies, could be applied to explore, enhance and disseminate those qualitative changes in behaviour within households that positively affect children's literacy development. In the process, it aimed to explore whether media representations that reflect the stories of parents trying out new literacy practices can create authentic, endogenous messages that resonate with people in similar circumstances, and can stimulate debate around the issue.
Keywords: Communication in economic development -- South Africa -- Makhanda; Literacy -- South Africa -- Makhanda; Literacy programs -- South Africa -- Makhanda; Education -- Parent participation -- South Africa -- Makhanda; Intsomi Project